2008
DOI: 10.1093/brain/awn310
|View full text |Cite
|
Sign up to set email alerts
|

Impaired efficacy of spinal presynaptic mechanisms in spastic stroke patients

Abstract: Pathophysiological mechanisms underlying spasticity have been the subject of many studies. These studies performed in various kinds of spastic patients have revealed abnormalities in many spinal pathways controlling motoneurone discharge. Unfortunately, the pathophysiological mechanisms responsible for the development of spasticity remains nevertheless largely unknown since most of the previous studies failed to reveal a link between the characteristics of spasticity (severity, time course) and that of the dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 56 publications
7
84
2
7
Order By: Relevance
“…Previous studies have revealed a significant positive correlation between reduced post-activation depression and spasticity severity 6,7 . Our results provide additional evidence for this relationship.…”
Section: A B Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies have revealed a significant positive correlation between reduced post-activation depression and spasticity severity 6,7 . Our results provide additional evidence for this relationship.…”
Section: A B Discussionmentioning
confidence: 96%
“…H-reflex depression is striking at short breaks (1-2 s between two successive stimulations). In contrast, the depression is not obvious when the stimulation intervals are 8 s or longer 7 . Decreased synaptic neurotransmitter release may be responsible for the depression, which is most obvious in resting individuals and is weak or absent when the tested muscle is voluntarily activated 8,10 .…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…These alterations may be caused by a loss of supraspinal control. In these conditions, treatment that aims to modulate the excessive impulses or the system of inter neurons becomes useful 34 . Activating large diameter afferent nerve fibers through TENS may modulate interneuron activities in several spinal segments, which then activate inhibition mechanisms of the presynaptic nerve 17 .…”
Section: Tensmentioning
confidence: 99%